(untitled) (Práxis Educativa, 2024)
The implementation of writing through digital tools is an important challenge for the teaching-learning process. Under this premise, the general objective of the research was to analyze the collaborative production of essays, through Google Docs. 32 teachers in training of pedagogy in basic education participated, selected through intentional non-probabilistic sampling. Developed under a mixed approach, the study had a descriptive scope. The data collection was carried out through three procedures: observation and recording of interactions, analysis of virtual feedback and analysis of responses to an online questionnaire. Among the main findings are difficulties to organize time efficiently, impediments to agree on points of view, obstacles to making decisions in remote environments and limitations for the selection of information, for the choice of arguments incorporated in the essay and for the group reflections. Keywords: Virtual learning environment. Collaborative writing. Didactic strategy.